2021
DOI: 10.2196/23190
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App–Based Remote Patient Monitoring in Acute Medical Conditions: Prospective Feasibility Study Exploring Digital Health Solutions on Clinical Workload During the COVID Crisis

Abstract: Background Digital remote patient monitoring can add value to virtual wards; this has become more apparent in the context of the COVID-19 pandemic. Health care providers are overwhelmed, resulting in clinical teams spread more thinly. We aimed to assess the impact of introducing an app-based remote patient monitoring system (Huma Therapeutics) on a clinician’s workload in the context of a COVID-19–specific virtual ward. Objective This prospective feasib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…Overall, we found that the EWAS mobile app was feasible to use, based on the fact that the consistent use by 69% of the participants was similar to findings in other settings where digital screening tools were adapted for early detection of COVID-19 [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 75%
“…Overall, we found that the EWAS mobile app was feasible to use, based on the fact that the consistent use by 69% of the participants was similar to findings in other settings where digital screening tools were adapted for early detection of COVID-19 [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 75%
“…They observed that the group with reminders tended to use the application more and send more tasks than those who did not, although the difference in pain control in both groups was not statistically significant. In a very recent study related to the post-hospitalisation follow-up of COVID-19 patients, Shah et al 24 analysed a digital solution that combines the use of a mobile application with a telephone monitoring centre to assess whether the application was able to reduce the flow of calls to this centre. They found that the group that used the application made, on average, half as many calls as the other group.…”
Section: Discussionmentioning
confidence: 99%
“…This solution typically involves self-monitoring at home, supplemented by frequent telephone contact. The incorporation of remote monitoring technology has been suggested as a way to further improve quality and lessen resource utilization 9 . Current technology now allows for enhanced monitoring and a more targeted approach to post-hospital care.…”
Section: Discussionmentioning
confidence: 99%